ANALISIS SEMIOTIKA KOMUNIKASI ROLLAND BARTES DALAM FILM KUCUMBU TUBUH INDAHKU - Yohanes Arie Kuncoroyakti (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The film, which was produced in 2018 and written by Garin Nugroho, won an award at the 75th Venice International Film Festival. In Indonesia, this film won 9 awards at film festivals. The existence of this film gets a lot of controversy in Indonesia, because of the LGBT issue. This study uses a communication semiotics approach with the Rolland Barthes method. Qualitative research methods with an interpretive paradigm are the basis for this research. The dominant eastern Javanese cultural value in this film is the cultural tradition of the lengger dancer. Juno as the main character in this film is interested in becoming a lengger dancer which is then opposed by the surrounding community, this is because the main character is a man. The inspiration for this film came from a choreographer who blended the lengger culture in East Java.